Follicular Dendritic Cell Sarcoma of the Omentum: Multidetector Computed Tomography Findings - Chien, Jerry Chin-Wei (The Korean Society of Radiology, 2013)
We report computed tomography (CT) findings for a rare case of follicular dendritic cell sarcoma of the greater omentum from a 47-year-old female patient. The tumor presented ash a palpable mass lesion in the umbilical region for the last two months. Multidetector CT scan of the abdomen showed a 14-cm soft-tissue mass with calcification and necrosis within the greater omentum. As a result, a follicular dendritic cell sarcoma should be considered in the differential diagnosis of a solitary omentum mass, especially one with coarse and chunk-like calcifications.